Urinary Levels of IL-1β and GDNF in Preterm Neonates as Potential Biomarkers of Motor Development: A Prospective Study - Rafael Coelho Magalhães; Janaina Matos Moreira; Érica Leandro Marciano Vieira; Natália Pessoa Rocha; Débora Marques Miranda; Ana Cristina Simões e Silva (Mediators of Inflammation)
Objectives. To evaluate the association between inflammatory biomarkers, neurotrophic factors, birth conditions, and the presence of motor development abnormalities in preterm neonates. Methods. Plasma and urinary levels of cytokines (IL-1β, IL-6, IL-10, TNF, and IL-12p70), chemokines (CXCL8/IL-8, CCL2/MCP-1, CCL5/RANTES, CXCL10/IP-10, and CXCL9/MIG), and neurotrophic factors (BDNF and GDNF) were evaluated in 40 preterm neonates born between 28 and 32 incomplete weeks of gestation, at four distinct time points: at birth (umbilical cord blood) (T0), at 48 (T1), at 72 hours (T2), and at 3 weeks after birth (T3). Biomarkers levels were compared between different time points and then associated with Test of Infant Motor Performance (TIMP) percentiles. Results. Maternal age, plasma, and urinary concentrations of inflammatory molecules and neurotrophic factors were significantly different between groups with normal versus lower than expected motor development. Higher levels of GDNF were found in the group with lower than expected motor development, while IL-1β and CXCL8/IL-8 values were higher in the group with typical motor development. Conclusion. Measurements of cytokines and neurotrophic factors in spot urine may be useful in the follow-up of motor development in preterm neonates.